Giant folliculosebaceous cystic hamartoma of the vulva: A rare occurrence. Issue 3 (20th July 2020) - Khan, Amena; Gowda, Chiranth; Vasudevan, Geetha; Rodrigues, Gabriel
Abstract : Giant FSCH of the vulva can be disfiguring, leading to sexual and psychological issues affecting quality of life. Total excision of the lesion is recommended.